its urgent please help
Attachments:
![](https://hi-static.z-dn.net/files/dfd/d5afefac08483d3360530f96334e07b5.jpg)
Answers
Answered by
2
sin^2 (u)=(1-cos2u)/2
=£sin^2 (3x)dx
=£(1-cos2 (3x)/2dx
=(1/2) £dx-(1/2) £cos6xdx
=£(1/2)dx-(1/2)(1/6) £cos6xdx
=(1/2)x-(1/2)sin6x+c
=£sin^2 (3x)dx
=£(1-cos2 (3x)/2dx
=(1/2) £dx-(1/2) £cos6xdx
=£(1/2)dx-(1/2)(1/6) £cos6xdx
=(1/2)x-(1/2)sin6x+c
Answered by
2
Attachments:
![](https://hi-static.z-dn.net/files/dff/1ccfc70a5e34af65168941099c0fabaf.jpg)
Similar questions